Efficient documentation and webmarketing strategies for DNAs - Axel Michaelowa; Naman Gupta (Hamburg Institute of International Economics (HWWA), 2005)
In accordance with the modalities and procedures for a Clean Development Mechanism (CDM) decided in Marrakech 2001, "Parties participating in the CDM shall designate a national authority for the CDM." Till date only 89 Parties have established their Designated National Authority (DNA). Capacity building and marketing the national CDM programmes to buyers of Certified Emission Reductions (CERs) or project investors is one of the important tasks of host countries. In that context, website development and hosting is a key outreach mechanism for DNAs to market their national CDM programme as well as improving their country's competitiveness on the global market. But also Annex I DNA websites can play a useful role, particularly for host country companies who want to assess the attractiveness of countries as buyers of CERs. As per the information available on the internet, only 26 Parties among which are 8 Annex I countries have set up official DNA websites which contain a variety of information related to CDM as well as climate change-related activities. As it has been observed that the organisation of most of the DNA websites and quality of information available can be improved and webmarketing tools seem not to have been used, we suggest a standard model structure of websites separately for DNAs of Non-Annex I and Annex I countries differentiated according to the size and CDM attractiveness of the host country.
Keywords: Q54; Q56; 330; CDM; DNA website; Non- Annex I countries; Annex-I countries; marketing; Umweltbehörde; Clean Development Mechanism; Klimaschutz; Staatliche Information; Telemarketing; Homepage; Welt